Exploring the social legacy of frequent wildfires: Organizational responses for community recovery following the 2018 Camp Fire. (15th February 2022) - Edgeley, Catrin M.
Abstract: The increased global frequency and scale of impactful and destructive wildfires has necessitated the reimagination of recovery assistance in affected communities. Unequal experience with and access to resources to support recovery mean that organizations operating at different scales may provide varying types of assistance after fire, particularly in rural areas. The US state of California has experienced several notable wildfire events in the past decade, including the 2018 Camp Fire that broke state and national records associated with the losses it caused. Interviews with 45 individuals involved in post-fire recovery after the Camp Fire are examined here using structuration theory to understand varied organizational responses across scales. Interviews focused on understanding how different organizations respond to wildfire disasters before examining the legacy that frequent wildfires have had on wildfire recovery response at local, state, and national scales. The rigidity of national and federal level organizations required local and state level organizations to rapidly adapt to support context-specific recovery needs. Local organizations accessed knowledge gathered during other recent wildfire disasters to navigate local impacts and needs. Without formal means to document perishable knowledge gathered during past wildfires, lessons learned may not be harnessed during future hazard events. Future recovery efforts after wildfire will benefit from proactive efforts to foster cohesion across responding organizations, opportunities to share and apply knowledge gathered through experiential learning, and pre-determined methods for communicating how non-local responses should take local social contexts into consideration.